Baculoviruses hijack host midgut-derived tachykinin to regulate phototactic climbing behavior and promote viral transmission - Lin Zhu; Xiaoming Liu; Limei Cai; Zhen Li; Chenxi Liu; Xiaoxia Liu (Proceedings of the National Academy of Sciences, 2026)
Baculoviruses are large DNA viruses that mainly infect insects. During infection, viral egress from midgut cells and subsequent behavior changes lead to terminally infected insects migrating to higher elevations on plant branches or tree limbs. However, the neural mechanisms driving this hyperactivity remain poorly understood. In this study, we demonstrate that the climbing behavior of Helicoverpa armigera larvae enhances the dispersal of Helicoverpa armigera single nucleopolyhedrovirus (HearNPV). Our findings reveal that HearNPV triggers a calcium response in enteroendocrine cells, leading to the release of midgut-derived tachykinin (TK). Released TK activates its receptor (TKR) in the brain, thereby promoting phototaxis and climbing behavior. Additionally, HaTTD14 functions as a downstream regulator of the TK–TKR signaling pathway. These results provide insights into the neural and molecular mechanisms driving baculovirus-induced hyperactivity, which aids in viral transmission.